Actuator energy and drag minimization of a blended-wing-body with variable-camber continuous trailing-edge flaps. Issue 9 (1st September 2020) - Zhao, Wei; Kapania, Rakesh K.
Abstract : This article conducts a multiobjective optimization study for minimizing both the actuator energy and the total drag of a NASA N + 2 aircraft, the Blended-Wing-Body (BWB), during cruising, by using the three-segment Variable-Camber Continuous Trailing-Edge Flap (VCCTEF) proposed by NASA. The metric for the electric drive actuators' energy for the BWB during cruising is characterized by summing the absolute hinge moments for all actuators. A local minimum is easily obtained for the optimization problem with a least absolute sum cost function when using a gradient-based optimizer. The minimization of the total actuator energy is converted to a linear programming problem by treating the absolute hinge moments as design variables. The induced and profile drags are considered to be the largest two contributions to the total drag. Design variables for the flap rotations and the absolute hinge moments with different orders of magnitude are scaled with respect to their maximum bounds in the optimization study to avoid numerical problems. Different VCCTEF configurations of varying deflection profiles and degrees of actuation independence and traditional flaps are studied and their performance is compared. For the BWB with four representative fuel levels, 80, 50, 20 and 0% of the maximum fuel loads, all during cruising, multiobjective optimization studies show that the VCCTEF with three individual segments can achieve a minimal total drag for the BWB while requiring a minimal total actuator energy to maintain its optimal shape for the minimal total drag.